The upside of irrationality [compact disc, unabridged] : the unexpected benefits of defying logic at work and at home - Ariely, Dan (Harper Audio, 2010)
Focusing on our behaviors at work and in relationships, Dan Ariely offers insights and surprising truths about what motivates us on the job, how one unwise action can become a long-term habit, how we learn to love the ones we're with, and more.